The Difference in the Effects of Theobromine Solution at Concentrations of 1%, 5%, and 10% on the Shear Bond Strength of Composite Resin and Dentin - Angela, Carline; Prahasti, Anastasia; Elline (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: The use of composite resin as a restorative material poses challenges in creating optimal adhesive bonds with dentin, particularly due to the presence of the smear layer. A cavity cleanser is required to remove the smear layer and enhance adhesive strength. Chlorhexidine is considered the gold standard cavity cleanser, but it has toxic effects on the pulp. Theobromine, a natural compound derived from cocoa beans, has the potential to serve as a safer alternative with low toxicity. Material and Methods: This in vitro experimental study employed five treatment groups: aquadest, 2% chlorhexidine, 1% theobromine, 5% theobromine, and 10% theobromine. A total of 25 premolar tooth samples were used. Shear bond strength was measured using a universal testing machine. Data were analyzed with a One-Way ANOVA statistical test. Results and Discussions: The highest shear bond strength value was observed in the 5% theobromine group (5.53 MPa). There was no significant difference among the treatment groups (p > 0.05). Conclusion: The 5% theobromine solution yielded the highest mean shear bond strength value compared to other groups, although the difference was not statistically significant. These findings suggest that theobromine has potential for further investigation as a candidate cavity cleanser.